Window of risk for emigration of Wheat streak mosaic virus varies with host eradication method - Jiang, W.; Peterson, Dallas E. (Dallas Edward); Harvey, Tommy Larkin; Bowden, Robert L.; Fang, L.; Garrett, Karen A. (My University, 2007)
The wheat curl mite (WCM), Aceria tosichella, the vector of Wheat streak mosaic virus (WSMV), often survives the summer on volunteer wheat (Triticum aestivum) and may disperse from this “green bridge” in fall to newly planted winter wheat. Because some methods for managing volunteer wheat do not directly kill WCM, there is a window of risk for WCM and WSMV emigration after management has been applied. WCM survival in response to treatment of wheat by glyphosate, paraquat, stem cutting, and withholding water was measured in greenhouse experiments to determine how this window of risk for emigration varies with management. WCM populations on plants treated with paraquat or stem cutting decreased from the beginning of the sampling period. WCM populations on plants treated with glyphosate or that received no water increased up to 3 days after application and then decreased by 10 days after application. If glyphosate is used to manage volunteer wheat infested with WCM, it should be applied well before wheat is planted in fall. WCM in declining populations tended to be in an upright posture that could facilitate emigration via wind. The total green leaf area was strongly correlated with the number of WCM for treated plants and could be used in the field to predict the posttreatment survival of mites that pose a risk of emigration.
Citation: Jiang, W., Garrett, K., Peterson, D., Harvey, T., Bowden, R., Fang, L. (2007). The Window of Risk for Emigration of Wheat streak mosaic virus Varies with Host Eradication Method. Plant Disease, 89(8), 853-858. https://doi.org/10.1094/PD-89-0853
Keywords: Wheat streak mosaic virus; Host eradication method; Wheat curl mite; Volunteer wheat